Analysis of Google Classroom's Online Learning Motivation on Mathematics Subjects - Apriana, Anik; Hidajat, Djatmiko (Universitas Negeri Surabaya, 2020)
This article aims to describe students' motivation for online learning using Google Classroom in mathematics. In this study, the method used is descriptive qualitative, involving 21 senior high school students in Sukoharjo. The data collection techniques used were questionnaires and interviews. The results showed that the motivation to learn online Google Classroom in mathematics is influenced by internal and external factors. The first internal factor, namely the desire and desire above 60% indicates a good category, supported by the results of interviews that students have the desire and desire to succeed after using learning using Google Classroom. Second, there is an encouragement and learning need above 70% in a good category, indicating that students are motivated to learn. With the interview results, students answered that the ease of using Google Classroom provided a special experience in the student learning process that gave rise to a desire and encouragement to learn. The external factor, namely the existence of interesting activities in learning Google Classroom, is considered quite effective. From the four statements given, it reaches an average of 65%, the category is sufficient which indicates that Google Classroom can be accepted by studentsKeywords: Online learning, Google Classroom, Motivation